Analysis of Students’ Ability and Multiple-Choice Numeracy Test based on Item Difficulty Using Rasch - Churun Lu'lu'il Maknun; Ajeng Wahyuni; Irwani Zawawi (Jurusan Tadris Matematika UIN Siber Syekh Nurjati Cirebon, 2023)
The purpose of this research is to evaluate learners' numeracy knowledge. This study looked into how university students were taught math skills. The research strategy used in this investigation was quantitative. Rasch Model study was used for the data study. The first research question's goal was to assess the numeracy exams' item difficulty characteristics using the Rasch Measurement Model, and The second research topic's goal was to look into the student's numeracy test performance parameters. According to the study, performing a range of calculations to add, subtract, and multiply as well as calculating and interpreting mean in a variety of contexts were the skills that students found the most difficult to master. The pupils perform exceptionally well when they identify and contrast information and data in tables. The outcome makes it possible to pinpoint each examinee's testing assets and weaknesses; this diagnostic should be applied to raise students' numeracy standards. The level of numeracy can be improved using two important methods. Teaching strategy: Math instructors should adapt their course materials to the students' learning styles